Features of the morphometric structure of Strongyloides papillosus (Wedl, 1856) isolated from sheep - Мельничук, В. В.; Сорокова, С. С. (Scientific Progress & Innovations, 2018)
In modern conditions of farming, the sheep industry can be one of the pеrspective for recovery and its development from the point of view of increasing the effective using of land, the level of employment of the population, providing the national sector of processing and light industry with raw materials with medicinal properties. One of the reasons that reduces the efficiency of sheep breeding is helminthic diseases, including stronhyloidosis. As a result of this invasion, the young species lose in growth and weight, changes quality of wool, sometimes the death of animals occurs. Therefore, the determination of the features of the identification of this causative agent is an actual direction of scientific research. The purpose of the work was to study the features of the species identification of parthenogenetic females Strongyloides papillosus isolated from sheep. The task of the research was to explore the morphological features of the structure of the stronhyloid species of the S. papillosus species; to establish metric species characteristics of nematodes of S. papillosus species. The research was conducted during 2016–2018 in the laboratory of the Department of Parasitology and Veterinary and Sanitary Expertise at Poltava State Agrarian Academy. The collection of nematodes was carried out by the method of complete helminthic autopsy of organs of the digestive tract of dead or slaughtered sheep that came to hand from farms of Poltava, Kyiv and Zaporizhzhia regions. As a result of parasitological research of small intestines from slaughtered sheep, a stronhyloidosis agent of the species Strongyloides papillosus (Wedl, 1856) was identified, which is represented by a parthenogenetic parasitic female with specific morphological and metric characteristics. Differential morphological features of parasitic females S. papillosus are the structure of the anterior and tail end, vulva area, uterus, and the presence of interception in the area of the esophagus transition into the intestine. To increase the effectiveness of species identification of parthenogenetic females S. papillosus, 24 metric indicators are offered. Prospects for further research are the determination of the biological qualities of Strongyloides papillosus in the seasonal aspect.